A critical investigation into the antibiotic sterilization of heart valve homografts - Waterworth, Pamela M. (1974)
Waterworth, Pamela M., Lockey, Eunice, Berry, E. M., and Pearce, Helen M. (1974).Thorax, 29, 432-436. A critical investigation into the antibiotic sterilization of heart valve homografts. Sterility tests of homograft heart valves sterilized by antibiotics were found to be invalidated by carry-over of the antibiotics. A method was devised to test the efficacy of different antibiotic mixtures using membrane filters. Fifty-five organisms, including 13 species, were tested, and sterility was achieved with only 35.